SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA BANTUAN PROGRAM KELUARGA HARAPAN BAGI RUMAH TANGGA MISKIN - Harlinda L Harlinda L (AkMen JURNAL ILMIAH, 2009)
A Decision Support System for Determining the Fund Receiver Of Program Keluarga Harapan (PKH) is a computer based application that can be used by the government, especially by the Statistic Center Bureau (BPS) to select poor families who are eligible to the fund to increase their health and education services. This system provides many scoring criterias for the selection. These criterias are choosen and formulated by looking at many relevant factors, and modeled mathematically in order to give result, that helps the decision maker in deciding the fund receivers of Program Keluarga Harapan.